The Impact of AI Integration on Efficiency and Performance in Financial Software Development - Alok Gupta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This comprehensive study investigates the transformative effects of integrating artificial intelligence (AI) technologies into financial software development processes. As the financial sector increasingly relies on sophisticated software solutions, the potential for AI to enhance efficiency, accuracy, and overall performance in development cycles has become a subject of significant interest. This research examines various AI applications within financial software development, including automated code generation, intelligent debugging, predictive maintenance, and AI-assisted testing. Through a mixed-methods approach combining quantitative analysis of development metrics and qualitative insights from industry professionals, we evaluate the tangible impacts of AI integration on key performance indicators such as development speed, code quality, and resource utilization. Our findings reveal substantial improvements in efficiency and performance across multiple dimensions of the software development lifecycle, while also highlighting challenges and considerations for successful AI implementation. This study contributes to the growing body of knowledge on AI in software engineering and provides valuable insights for financial institutions and software development teams considering or currently implementing AI-driven development strategies.